The Dark Side of Green HRM: Multigroup Analysis of Employee Responses to Internal Greenwashing - Riski Eko Ardianto; Retno Purwani Setyaningrum; Ahmad Johan (Business and Applied Management Journal, 2026)
This study aims to examine how internal greenwashing within Green Human Resource Management (GHRM) affects employee green creativity through the psychological mechanism of green fatigue, while also testing the moderating role of competitive green gamification and group differences based on green value orientation. Drawing on Conservation of Resources (COR) theory and Self-Determination Theory, this study conceptualizes perceived greenwashing as an internal organizational stressor that depletes employees’ psychological resources and weakens intrinsic motivation. A quantitative survey was conducted among 556 hotel employees in the Java–Bali region, Indonesia, using a non-probability purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct, mediating, moderating, and multigroup effects. The results show that perceived greenwashing increases green fatigue and reduces employee green creativity, both directly and indirectly. Competitive green gamification strengthens the effect of greenwashing on green fatigue. Multigroup analysis further reveals that these effects are stronger among employees with high green value orientation. This study contributes to GHRM literature by shifting the focus from external to internal greenwashing and highlighting its psychological and behavioral consequences.